'To see the world with different eyes': thoughts on existential orientation in socio-economic education. (26th March 2020) - Graupe, Silja
This paper outlines the tectonic disturbance which would occur in (and for) neoclassical economics if it were oriented to the existential nature of human economic activity. The point is not to entirely negate the standard teaching but to re-establish its actual questionability and at the same time to develop fundamental alternatives, particularly from an epistemological standpoint. Existential philosophy originally emerged through a crisis, where philosophy found itself trapped between speculative idealism and scientific positivism - both of which tended to completely ignore the problems of real urgency for ordinary people. In a certain sense I see a similar crisis in economics today, one that adopts a very specific form. My contribution lays out for the first time an explicit existential orientation for socio-economic education, fostering awareness of and creative responses to the issues presented.